Beyond Relationship Management: The Mediating Role of Customer Engagement in Driving Customer Retention: Melampaui Manajemen Hubungan: Peran Mediasi Keterlibatan Pelanggan dalam Mendorong Retensi Pelanggan - Ade Wahyudistira; E.R Taufik; Liza Mumtazah Damarwulan (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2026)
A Despite the widespread adoption of customer relationship management (CRM), its ability to directly enhance customer retention remains uncertain. This study investigates whether customer engagement explains how CRM translates into retention outcomes. Using survey data from 117 respondents, the proposed model was tested with partial least squares structural equation modeling (PLS-SEM) in SmartPLS. The results show that CRM does not exert a statistically significant direct effect on customer retention (β = 0.223, p = 0.067). However, CRM significantly strengthens customer engagement (β = 0.676, p < 0.001), which in turn positively affects customer retention (β = 0.599, p < 0.001). Moreover, the indirect effect of CRM on customer retention through customer engagement is significant (β = 0.405, p < 0.001), indicating that engagement is the primary pathway through which CRM drives retention. The model explains 58.8% of the variance in customer retention (R² = 0.588). These findings extend CRM research by showing that retention is achieved not through CRM alone, but through CRM practices that actively cultivate meaningful customer engagement and long-term relational value.